COMPARATIVE ANALYSIS BETWEEN ANALOG AND AUTOMATED METHODS FOR GEOMORPHOLOGICAL COMPARTMENTATION AND OBTAINING MORPHOMETRIC DATA - Gouveia, Isabel Cristina Moroz-Caccia [UNESP]; Ross, Jurandyr Luciano Sanches [UNESP] (Univ Estado Rio Janeiro, 2023)
The research carried out a comparison of the Relief Dissection Index (IDR) of the geomorphological map of the state of Sao Paulo elaborated from analogical techniques, and data obtained in an automated way with the application of the Relief Concentration Index Roughness - ICR (. Visual similarities were observed between the results obtained in the ICR and IDR. However, when carrying out the spatial analysis in a GIS (Geographic Information System) environment, it was observed that the similarities between polygon boundaries are restricted to 36.2%. The comparison indicated 37% of coincident areas, 41% of classifications one class above or below, and 22% of inconsistencies. Regarding the delimitation of morphoscultural subunits, correlations ranging from 67.29 to 92.42% were obtained. For the whole area, the percentage of similarities is 89.15%. The results indicate that the ICR has great potential, however, although it can be used for previous compartmentalization of homogeneous spatial units, it must be complemented with field surveys and qualitative analyzes since the use of morphometric data alone can result in data that do not contemplate the complexities of the physical environment.
Keywords: Geomorphological Mapping; Analog and automated methods. Morphometry; Relief Dissection Index; Roughness Concentration Index